La chambre bleue - Costes, Paul. (France : l'atelier documentaire, 2015)
Since this father's death in 2002, Paul Costes has often heard the now commonplace admonition that it is time to move on from grieving. Mixing Super-8 home movies and recent interviews with members of his family—who are also invited to a meal to commemorate the tenth anniversary of his father’s death—the filmmaker has produced a digressive comedy that is also a letter to the departed.
Verzio Film Festival Submission
Keywords: Documentary films